Risk Management Planning for Agricultural Business Owners - Martie Gillen; Beatrice Pierre (EDIS, 2019)
Risk identification is the beginning point for risk management planning because solution identification begins with knowledge of the problem. This 4-page document presents questions to consider regarding production risk, price or market risk, financial risk, legal risk, and human risk. Written by Martie Gillen and Beatrice Pierre, and published by the UF/IFAS Department of Family, Youth and Community Sciences, August 2019. http://edis.ifas.ufl.edu/fy1485